PERTUMBUHAN DAN CARA KERJA DPR-RI PASCA REFORMASI - Yamin, Saefullah; Nurwahyuni, Nurwahyuni (Yustitia, 2020)
Post reformation of the role and function of the House of Representatives of Republik Indonesaian (DPR RI) is returned to its corridor as a legislative institution that runs the legislative function (making laws/constitution), besides running budgeting fungction together with the president, and the oversight function of the implementation of the law and the budget in the administration of government carried out by the executive. Related to the lack of productivity of The House of Representatives (DPR) to carry out the legislative function, The performance evaluation of this legislation is not only seen in terms of the quantity of products made but its quality is also an important factor in assessing legislation products. The identification problems in this research are: What is the Position of the House of Representatives in the 1945 Constitution of the State of the Republic of Indonesia, and What is the Process of the Growth of the Post-Reformation House of Representatives. In this research the library research method will be used or library research. Regarding this kind of research it is usually also called "Legal Research" or "Legal Research Instructionâ€. The position of The House of Representatives (DPR) after the amendment of the 1945 Constitution four times turned out to further strengthen its existence as the sole legislator. Although in the 1945 Constitution the amendment results also gave the President authority, but the authority he owned was not as big as The House of Representatives (DPR). And the process of the growth of the House of Representatives (DPR) Post-Reformation has strengthened the authority of the legislative instituion, in this case the House of Representatives of Republik Indonesian (DPR-RI) to maximize its role and function as a check and balances institution, after being strengthened, the House of Representatives (DPR) becomes tyrannical over the executive even over the state, because of its power and authority so great.